2021
DOI: 10.2478/aiht-2021-72-3559
|View full text |Cite
|
Sign up to set email alerts
|

Work from home and musculoskeletal pain in telecommunications workers during COVID-19 pandemic: a pilot study

Abstract: One of the side-effects of the COVID-19 pandemic is a global change in work ergonomic patterns as millions of people replaced their usual work environment with home to limit the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) infection. The aim of our cross-sectional pilot study was to identify musculoskeletal pain that may have resulted from this change and included 232 telecommunications company workers of both genders [121 (52.2 %) men aged 23–62 (median 41; interquartile range 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 16 publications
0
44
0
18
Order By: Relevance
“…2021) De acordo com um estudo feito na Índia, a parte superior das costas e membros superiores foram os mais afetados, já as dores na parte inferior das costas e membros inferiores diminuíram significativamente após o início da pandemia (MAJUMDAR et al, 2020). A maior prevalência de dores no pescoço e parte inferior das costas, principalmente em mulheres, foi relatada em outros dois estudos (RADULOVIĆ et al, 2021) (PRIETO-GONZÁLEZ et al, 2021. Outro estudo feito nos Estados Unidos, apontou um aumento na prevalência de dor no pescoço, parte superior das costas, quadril e joelho (GULER et al, 2021).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…2021) De acordo com um estudo feito na Índia, a parte superior das costas e membros superiores foram os mais afetados, já as dores na parte inferior das costas e membros inferiores diminuíram significativamente após o início da pandemia (MAJUMDAR et al, 2020). A maior prevalência de dores no pescoço e parte inferior das costas, principalmente em mulheres, foi relatada em outros dois estudos (RADULOVIĆ et al, 2021) (PRIETO-GONZÁLEZ et al, 2021. Outro estudo feito nos Estados Unidos, apontou um aumento na prevalência de dor no pescoço, parte superior das costas, quadril e joelho (GULER et al, 2021).…”
Section: Resultsunclassified
“…Diante do exposto, foi possível identificar diversos fatores que impactaram negativamente na saúde de indivíduos mantidos sob regime de home office, durante a pandemia da Covid-19. Ganho ponderal, desenvolvimento de distúrbios musculoesqueléticos e diminuição do bem estar mental foram algumas das consequências encontradas (RADULOVIĆ et al, 2021).…”
Section: Conclusãounclassified
See 2 more Smart Citations
“…In this study, when teleworking preference and teleworking frequency were adjusted, a teleworking preference was associated with work functioning impairment whereas the teleworking frequency was no longer associated with work functioning impairment. Some studies have suggested that teleworking is associated with poor health conditions, such as depression and musculoskeletal pain 31,32 . Key to detecting signs of work functioning impairment would be to follow up on the health conditions of employees who frequently telework.…”
Section: Discussionmentioning
confidence: 99%